Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have just started learning about differential equations, as a result I started to think about this question but couldn't get anywhere. So I googled and wasn't able to find any particularly helpful results. I am more interested in the reason or method rather than the actual answer. Also I do not know if there even is a solution to this but if there isn't I am just as interested to hear why not.

Is there a solution to the differential equation:

$$f(x)=\sum_{n=1}^\infty f^{(n)}(x)$$

share|cite|improve this question
Assume everything works well, and differentiate the equation. Looking sharply, you will see a first order ODE emerging. – Daniel Fischer Feb 6 at 11:45
If you differentiate the equation, and assume that everything behaves nicely, what equation do you obtain? – Daniel Fischer Feb 6 at 11:50
Right. And now look, how does that right hand side differ from the original right hand side? – Daniel Fischer Feb 6 at 11:56
@DanielFischer By $f'(x)$. Which gives $f'(x)=f(x)-f'(x)$ therefore $f(x)=2 f'(x)$. Ah Ok got it. Thank you very much!! – o.comp Feb 6 at 11:58
And don't forget the boring solution (for all homogeneous linear differential equations): $0$. – Eric Towers Feb 6 at 21:04
up vote 30 down vote accepted

$f(x)=\exp(\frac{1}{2}x)$ is such a function, since $f^{(n)}=2^{-n} f(x)$, you have

$$\sum_{n=1}^\infty f^{(n)}(x)=\sum_{n=1}^\infty 2^{-n}f(x)=(2-1)f(x)=f(x)$$

This is the only function (up to a constant prefactor) for which $\sum_{n}f^{(n)}$ and its derivatives converge uniformly (on compacta), as $$f'=\sum_{n=1}^\infty f^{(n+1)}=f-f'$$ follows from this assumption. But this is the same as $f-2 f'=0$, of which the only (real) solutions are $f(x)= C \exp{\frac{x}{2}}$ for some $C \in \mathbb R$.

share|cite|improve this answer
Being little pedantic: the constant zero function would work too. – DBS Feb 6 at 14:20
@DBS this is covered by $C=0$. – s.harp Feb 6 at 14:20
Oops you are right. Sorry my bad. – DBS Feb 6 at 14:42
Does it remain to determine whether there are some more solutions where the convergence of the series is (point-wise but) not uniform, then? – Jeppe Stig Nielsen Feb 7 at 9:24
It remains to be determined :) – s.harp Feb 8 at 10:30

Differentiate both sides to get $f'(x)=f''(x)+f^{(3)}(x)+...$

So the starting equation becomes $f(x)=f'(x)+f'(x)\Rightarrow f(x)=2f'(x)$

Multiply now both sides by $e^{-\frac{x}{2}}$ and this becomes
So $f(x)=ce^{\frac{x}{2}}$

share|cite|improve this answer

the question means: $$y-y'-y''-y'''-......y^n=0$$ the differential equation is homogeneous and the characteristics equation is $$1-r-r^2-r^3-.......r^n=0$$ $$r(1+r+r^2+r^3+....)=1$$ by using the geometric series (r<1) $$\frac{r}{1-r}=1$$ $$r=1-r$$ $$r=\frac{1}{2}$$ so the function is $$y=Ce^{\frac{x}{2}}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.